Evaluation of the CSE-UCLA Model on Vocational High School Entrepreneurship Learning in Facing the Industry Era 4.0 - Sumarno Sumarno (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to analyze the effectiveness of entrepreneurship learning at vocational high schools in Pekanbaru, Riau in facing the industrial era 4.0. This study is an evaluation study using the CSE-UCLA model. The research was conducted at 6 publics and 6 private vocational schools in Pekanbaru by presenting questionnaires, observations, interviews, and documentation. The data were analyzed descriptively and by comparison. The results of the study show that; 1) entrepreneurship learning at vocational high schools in Pekanbaru has not been effective from the aspect of entrepreneurship and the industrial era 4.0; 2) learning objectives do not include important entrepreneurial attitudes and the requirements of the industrial era 4.0 (leadership, independent, critical, creative, and innovative); 3) the implementation of entrepreneurship learning in general still has not carried out activities that create leadership, decision making, creativity, and innovation as well as flexibility of thinking; 4) entrepreneurial learning outcomes which is entrepreneurial knowledge competencies are generally still classified as lacking so that they do not support flexibility of thinking. 5) The entrepreneurial intention of vocational high school students in Pekanbaru is generally still low so there is no need for entrepreneurship challenges and the industrial era 4.0, namely live independently.